Cyber security awareness among employees of MSC Cyberport Sdn. Bhd. Johor / Nurul Hazirah Azali - Azali, Nurul Hazirah (2018)
Cyber security are be used as risk technologies to defend the users assets, cyber environment and organization by collect the tools, policies, security concepts, security safeguards and also guidelines. The reason researcher does this study because this study has not been done in this company before. The purpose of this study is to explore cyber security awareness among MSC Cyberport Sdn Bhd employees. The problem statement for this study is this company deals with customers', tenants' and government data and information all the time, and that need to be protected. MSC Cyberport Sdn Bhd should provide cyber security awareness among their employees. This was observed during the internship period. The method for this- study is qualitative study, where interview sessions were conducted among the employees of this company. The usage of qualitative is to understand the level of cyber security awareness and to explore the ways in order to create cyber security awareness among MSC Cyberport employees. The findings show that the employees have different level of cyber security awareness and have limited knowledge about cyber security. Thus, the company need to enhance their cyber security awareness as the position of the employees to protect data and information from cyber attacks or hacking victims that can give negative impression towards the companys reputation.